If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (v + -1)(v + -6) = 0 Reorder the terms: (-1 + v)(v + -6) = 0 Reorder the terms: (-1 + v)(-6 + v) = 0 Multiply (-1 + v) * (-6 + v) (-1(-6 + v) + v(-6 + v)) = 0 ((-6 * -1 + v * -1) + v(-6 + v)) = 0 ((6 + -1v) + v(-6 + v)) = 0 (6 + -1v + (-6 * v + v * v)) = 0 (6 + -1v + (-6v + v2)) = 0 Combine like terms: -1v + -6v = -7v (6 + -7v + v2) = 0 Solving 6 + -7v + v2 = 0 Solving for variable 'v'. Factor a trinomial. (1 + -1v)(6 + -1v) = 0Subproblem 1
Set the factor '(1 + -1v)' equal to zero and attempt to solve: Simplifying 1 + -1v = 0 Solving 1 + -1v = 0 Move all terms containing v to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + -1v = 0 + -1 Combine like terms: 1 + -1 = 0 0 + -1v = 0 + -1 -1v = 0 + -1 Combine like terms: 0 + -1 = -1 -1v = -1 Divide each side by '-1'. v = 1 Simplifying v = 1Subproblem 2
Set the factor '(6 + -1v)' equal to zero and attempt to solve: Simplifying 6 + -1v = 0 Solving 6 + -1v = 0 Move all terms containing v to the left, all other terms to the right. Add '-6' to each side of the equation. 6 + -6 + -1v = 0 + -6 Combine like terms: 6 + -6 = 0 0 + -1v = 0 + -6 -1v = 0 + -6 Combine like terms: 0 + -6 = -6 -1v = -6 Divide each side by '-1'. v = 6 Simplifying v = 6Solution
v = {1, 6}
| 182.89=6.85c | | 4x^3-22x^2+16x+14=0 | | 1.8(-.2x-1.8)+5.5x=27.6 | | 49+x^2=625 | | ((1)2/3)y=15 | | x=-2-12 | | -71(z-29)=z+54 | | 42x+2=180 | | -21=6n | | -3+6u=-2u+7u+7 | | 5x/4=x/12-x/2 | | 9t=-12 | | 4-(3x-2)=x-10 | | 4.70-b=4.75 | | 1/2/3y=15 | | p-31=-21 | | 4.70-b=4.6 | | p=1 | | x-1/111/2 | | (-5s^2t^2)(3st^3)= | | (8c+d)(2c+3d)= | | 10y-5-5y=15 | | .25x+20=-30 | | y-1/5=5/7 | | 12=q+2 | | 4(x+6)+18x=134 | | 6+[8x-3]=12 | | 1+p=-5-2p | | 8x^3-16x^2+6x=0 | | -x-1=-4x+5 | | 4/9=24/m | | 5u-w=u-6w |